The impact of internal financial factors on the size of loan portfolios - الشواح زاهد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research is to determine the effect of internal financial factors on the size of loan portfolios of private commercial banks in Syria during the period (2009-2016), where the behavior of the dependent variable (size of loan portfolios) and the independent variables represented in (profitability ratio, debt ratio, ratio Liquidity, total assets, capital adequacy ratio). The statistical analysis program (SPSS) was used to conduct the following statistical analysis tests: Analysis of variance to test the existence of statistical significance for each variable of the independent study, and gradient regression analysis to determine the variables that have the greatest impact on the study elements . The research concluded the following results: 1- The presence of a positive significant impact on the indebtedness ratio and the capital adequacy rate on the size of the Syrian private commercial banks ’loan portfolios. 2- The presence of a significant negative impact of the liquidity ratio on the volume of private Syrian commercial banks ’loan portfolios. 3- The absence of a significant impact on the profitability ratio (rate of return on property rights, rate of return on assets) and total assets on the size of private Syrian commercial banks ’loan portfolios. The research recommends the need for private Syrian commercial banks to increase capital adequacy rates in order to enable them to enter into longer-term, more profitable and higher risk lending areas, and to study the debt ratio in detail to ensure that it is used as a likely element to increase the size of loan portfolios, and not to exaggerate and exaggerate by them by maintaining liquidity. And the necessity for them to properly exploit their assets, which leads to increased revenues and reduced expenses, which in turn reflects positively on the size of their loan portfolios.